Mapping Global Research Trends on VAT and Tax Administration Using Bibliometric Analysis - Ramadhani, Dianya Mutiara (Maliki Interdisciplinary Journal, 2025)
This research intends to examine the trends and patterns in studies concerning Value Added Tax (VAT) and Tax Administration by utilizing a bibliometric method. Information was obtained from 1,000 academic articles listed on Google Scholar and Sinta through Harzing's Publish or Perish tool and was evaluated with VOSviewer software. A total of 474 pertinent journal articles published from 2020 to 2025 were found. The bibliometric visualizations displayed six primary groups addressing subjects like tax policy, innovation, accounting, renewable energy, and tax compliance. These results offer a detailed view of the global research environment regarding VAT and tax administration. This study also assists in pinpointing research deficiencies and prospects for scholarly cooperation among various countries and institutions